Clinical, pathological and therapeutic findings on lingual rhabdomyosarcoma in a dog - case report - Dias, F. G. G.; Santilli, J.; Magalhaes, G. M.; Calazans, S. G.; Pereira, L. F.; Mattos Junior, E.; Honsho, C. S.; Alves, C. E. F. [UNESP]; Dias, L. G. G. G. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The biological behaviour of the tumours vary according to the species in which they occur, its location within the cavity, clinical stage and histopathological nature. Lingual neoplasms are generally uncommon in companion animals. Rhabdomyosarcomas are malignant, solid, aggressive formations with high metastatic potential. The clinical signs are variable and a definitive diagnosis can only be reached through histopathological analysis of biopsy and necropsy specimen. In some cases, immunohistochemical study may be needed to confirm the diagnosis. This paper aims to highlight important points about this uncommon condition in dogs, using a case report of lingual rhabdomyosarcoma, which showed no evidence of metastasis after diagnosis, nor of local recurrence after surgical excision with a wide safety margin. It was concluded that early diagnosis, the correct interpretation of the complementary tests and the appropriate therapeutic approach contributed to improving the quality of life and survival of the patient in question.
Keywords: tongue; oral neoplasm; small animals